AKULAH ROTI HIDUP Analisis Homili ke-44 sampai dengan ke-47 Yohanes Krisostomus atas Injil Yohanes - Antonius Baur Asmoro (Jurnal Teologi (Journal of Theology), 2014)
The bread of life is the special theme in the Gospel of John. Even, among the Gospels, it is only the Gospel of John that gives this theme. Nowadays, there are many questions about the meaning of bread of life. Many scholars said that the bread of life has a connection with the eucharist. But, is there only one meaning of the bread of life? John Chrysostom dedicated his 44th homily to the 47th homily as the homily which tells about the bread of life. John Chrysostom offered another interpretation of the bread of life. For him, the bread of life tells about the Jesus himself facing the teaching of Arius (Arianism) that spreads in his service territory. The bread of life becomes an apology of the Nicean faith facing the Arianism. The emphasis is that the bread of life is the Son itself who has same nature (homo-ousios) with the Father. The faith of the Son guides all mankind to the ressurection and the everlasting life.